An apparently extended infrared counterpart to 1E 1740.7-2942 - Martí, Josep (2010)
We present the results of a revised search for the near-infrared counterpart to the microquasar 1E 1740.7-2942, which has eluded identification despite the many years elapsed since its discovery. By taking into account new astrometric information, we have been successful to identify a single near-infrared source, with apparent non-stellar morphology, whose position agrees well with that of the microquasar X-ray and radio-emitting core at the subarcsecond level. The possible implications of this finding with respect to the nature of 1E 1740.7-2942 are discussed.